Spiralize: an R package for visualizing data on spirals - Gu, Zuguang; Hübschmann, Daniel (Bioinformatics, 2022)
Spiral layout has two major advantages for data visualization. First, it is able to visualize data with long axes, which greatly improves the resolution of visualization. Second, it is efficient for time series data to reveal periodic patterns. Here, we present the R package spiralize that provides a general solution for visualizing data on spirals. spiralize implements numerous graphics functions so that self-defined high-level graphics can be easily implemented by users. The flexibility and power of spiralize are demonstrated by five examples from real-world datasets.
Advance access publication date: 26 November 2021
Gesehen am 26.09.2022